Physiological and stem cell compartmentalization within the Drosophila midgut - Marianes, Alexis (eLife Sciences Publications, Ltd, 2013)
The Drosophila midgut is maintained throughout its length by superficially similar, multipotent intestinal stem cells that generate new enterocytes and enteroendocrine cells in response to tissue requirements. We found that the midgut shows striking regional differentiation along its anterior-posterior axis. At least ten distinct subregions differ in cell morphology, physiology and the expression of hundreds of genes with likely tissue functions. Stem cells also vary regionally in behavior and gene expression, suggesting that they contribute to midgut sub-specialization. Clonal analyses showed that stem cells generate progeny located outside their own subregion at only one of six borders tested, suggesting that midgut subregions resemble cellular compartments involved in tissue development. Tumors generated by disrupting Notch signaling arose preferentially in three subregions and tumor cells also appeared to respect regional borders. Thus, apparently similar intestinal stem cells differ regionally in cell production, gene expression and in the ability to spawn tumors. DOI: http://dx.doi.org/10.7554/eLife.00886.001